The Relationship Between E-commerce Factors and Consumer Purchase Intention among Generation Z - Rodzalan, Shazaitul Azreen; Fauzi, Aniq Denial; Mohd Noor, Noor Nazihah (Research in Management of Technology and Business, 2023)
E-commerce becomes a popular platform in selling and buying since COVID-19 epidemic hit in worldwide. With exception, Malaysians were unable to carry out their routine activities, including selling and buying activity which consequently trigger a trend of buying and selling activity using E-commerce platform. Therefore, this research aims is to determine the dominant factor of E-commerce, determine the level of consumer purchase intention, and explore the relationship between E-commerce factors and consumer purchase intention. This study is quantitative in which the questionnaire has been used as the main instrument for data collection. The respondent in this study was a student of Generation Z from Universiti Tun Hussein Onn Malaysia (UTHM) in Parit Raja. The results of this study were analysed using descriptive analysis and correlation analysis. The study results show that all objectives and hypotheses have been achieved and accepted. Respondent agreed that price is the dominant factor in consumer purchase intention, while the level of consumer purchase intention is high on E-commerce platform. E-commerce characteristics influence customer purchase intent, according to the study. The respondent does not anticipate a low price, but it should be reasonable and satisfactory to the buyer. Suggestion for the future is the scope of the studies and data collection through the qualitative method, which can get more descriptive results and findings. In conclusion, the research is essential since it helps Malaysia discover what causes consumers to buy via E-commerce, one of the fastest-growing company sectors.